Environmental education and social cartography: experiences in a community of Holguín, Cuba - Gallardo Milanés, Olga Alicia; Martínez Gallardo, Laís; Reyes Bermudez, Angel (Sociedade & Natureza, 2020)
Social mapping is an important tool to develop environmental education actions in the community because it promotes the active and critical participation of various social actors. The objective of the research was to understand the contribution of social cartography to community environmental education from theoretical and practical budgets, for this we studied the process of environmental education developed in the Oscar Lucero community of Holguin-Cuba through the Green Map project. The research was conducted from a qualitative perspective, analyzing the reality from the complexity, interviews and surveys were conducted that allowed us to listen to the criteria of the people who participated in the environmental education process. The study allowed us to conclude that the social mapping used in the Oscar Lucero Moya community managed to potentiate new social relations with nature, in practice cooperation ties were strengthened through the articulation of actors and new knowledge was built that re-signified the context. In addition, a new worldview was assumed from a complex system approach, which favored the analysis of socio-environmental conflicts revealed as problems.